What Happens to Patients with Inflammatory Bowel Disease Who Are Intolerant to Thiopurines? - Helena Gensmyr-Singer; Pontus Karling (Inflammatory Intestinal Diseases, 2024)
Introduction: The clinical consequences for patients with inflammatory bowel disease (IBD) who stop treatment owing to side effects have not been fully investigated. Methods: This retrospective observational study aimed to compare patients who discontinued thiopurine treatment due to side effects with those who tolerated thiopurine treatment in the use of other IBD drugs, surgery, and fecal calprotectin values in the first 5 years after the start of thiopurine treatment. Results: The proportion of patients with IBD who initiated thiopurine treatment at our clinic was 44% (32% ulcerative colitis and 64% Crohn's disease) and 31% (n = 94) of those patients had to stop thiopurine treatment within 5 years due to side effects. Patients who discontinued thiopurine treatment due to intolerance were significantly older (median age 33 vs. 27 years, p = 0.003), significantly more often used prednisolone (89 vs. 76%, p = 0.009), and used to a lesser extent TNF inhibitors at the start of thiopurine treatment (3% vs. 9%, p = 0.062). Budesonide treatment and non-TNF inhibitor second-line therapy were significantly more commonly used in patients who discontinued thiopurine treatment owing to side effects, but there were no statistically significant differences in the use of other treatments. The proportion of patients with a median FC >200 μg/g was significantly higher during follow-up in patients with UC who discontinued thiopurine treatment owing to side effects. Conclusions: Patients who discontinued thiopurines owing to side effects were prescribed more budesonide and non-TNF inhibitor second-line therapy, but there were no differences in the use of TNF inhibitors, prednisolone, or surgery.